Technoscience and development: An anthropological critique of processes of technology transfer to the Third World - Joan Picas Contreras (Revista CIDOB d'Afers Internacionals, 2003)
Policies aimed at the development of the so-called Third World generally make technology transfer aimed at speeding up progress one of their priorities. Technology transfers by agents of development involve their introduction in a context different from the original one. The attempt to transform traditional societies based on the imperatives of a techno-scientific rationality created in the West and the imposition of our cultural model generates numerous contradictions. At very least, they ignore the competencies and knowledge of the target populations or relegate them to a subordinate position. The article raises the problems of technological transfer in the context of development policies. Based on the assumption that techo-science, nature and society are non isolated from one another, but interact to create a complex socio-technical web, it questions the most deeply rooted constructs of the techno-scientific discourse and suggests socio-technical alternatives.